Anti-corrosion thermal-insulation coating composition, coating and preparation method of coating layer of anti-corrosion thermal-insulation coating composition

By using the combination of microbead layered composite metal hydroxide composite material and epoxy resin, the existing anti-corrosion and thermal insulation coating process is solved, and effective corrosion and thermal insulation effect on the steel structure is achieved.

CN119859449AActive Publication Date: 2025-04-22CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202311370301.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-20
Publication Date
2025-04-22
Estimated Expiration
2043-10-20

AI Technical Summary

Technical Problem

The existing anti-corrosion insulation coating synthesis process is complex, has high cost, and is prone to corrosion problems in steel structures below 200℃.

Method used

By coating the layered composite metal hydroxide on the surface of the microbead surface, the dispersion performance of the coating and the ability to capture corrosive anions are improved by using a composition of a microbead layered composite metal hydroxide.

Benefits of technology

It achieves the improvement of corrosion protection performance of steel structures while meeting thermal insulation needs, and the process is simple, environmentally friendly and low-cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859449A_ABST
    Figure CN119859449A_ABST
Patent Text Reader

Abstract

The invention relates to the field of coatings, and discloses an anti-corrosion thermal-insulation coating composition, a coating and a preparation method of a coating layer of the coating. The anti-corrosion thermal insulation coating composition contains a microbead layered composite metal hydroxide composite material, epoxy resin and a curing agent, wherein the microbead layered composite metal hydroxide composite material comprises microbeads and layered composite metal hydroxide coating the surfaces of the microbeads; the microbeads are glass microbeads and / or ceramic microbeads; interlayer anions of the layered composite metal hydroxide are corrosion inhibition anions. The coating prepared from the anti-corrosion coating composition has good anti-corrosion and heat-insulation effects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of coatings, and in particular to an anti-corrosion and thermal insulation coating composition, a coating and a preparation method of the coating. Background Art

[0002] Layered composite metal hydroxides (LDHs), also known as hydrotalcites, have a three-dimensional crystal structure formed by the longitudinal orderly extension of nano-scale octahedral two-dimensional layers. The layers are composed of two or more divalent and trivalent metal hydroxides. The anions between the layers are used to make up for the charge balance of the layers. The interlayer anions of LDHs are exchangeable and are replaced by other anions during the preparation process, thereby being used as a carrier of corrosion inhibitors. The corrosion inhibitor anions contained in the LDHs interlayer are released by the stimulation of external corrosive media and can capture corrosive anionic substances such as Cl - , SO4 2- etc., thereby playing an anti-corrosion role. However, the layered composite metal hydroxides prepared so far all have serious stacking, resulting in a small specific surface area, which inhibits their ability to capture corrosive anions. Ceramic and glass microspheres are light in weight, low in thermal conductivity, have thermal insulation properties and good dispersibility, and can be used as thermal insulation fillers.

[0003] Patent application number CN104877484B discloses a modified polymer emulsion which is a compound of silica sol and polymer emulsion, and is used to prepare a water-based energy-saving thermal insulation coating for petrochemical oil tanks. The main function of this coating is thermal insulation. For steel structures below 200°C, corrosion under the insulation layer is prone to occur, and there is no targeted solution; Patent application number CN111534131B discloses a SiO2 aerogel modified thermal insulation coating, which also does not provide a targeted solution to the corrosion under the insulation layer; Patent application number CN111019424B discloses an epoxy silicone resin thermal insulation coating based on the principle of polymer structure design. This coating has certain anti-corrosion properties while achieving thermal insulation properties. However, the synthesis process is relatively complex and the cost is high. The petrochemical industry needs to use thermal insulation coatings on a large scale, and economic friendliness limits the use of the coating. Summary of the Invention

[0004] The purpose of the present invention is to overcome the problems in the prior art of complex synthesis process of anti-corrosion and thermal insulation coatings, high cost, and the problem that the coating prepared by the existing anti-corrosion and thermal insulation coatings is prone to corrosion of steel structures such as petrochemical and thermal pipelines below 200°C. An anti-corrosion and thermal insulation coating is provided. The anti-corrosion and thermal insulation coating can meet the insulation requirements while also improving the corrosion protection performance of steel structures. At the same time, its preparation process is simple and environmentally friendly.

[0005] In order to achieve the above-mentioned object, the present invention provides an anti-corrosion and thermal insulation coating composition on one hand, wherein the anti-corrosion and thermal insulation coating composition comprises a micro-bead layered composite metal hydroxide composite material, an epoxy resin and a curing agent, wherein the micro-bead layered composite metal hydroxide composite material comprises micro-beads and a layered composite metal hydroxide coated on the surface of the micro-beads;

[0006] The microbeads are glass microbeads and / or ceramic microbeads;

[0007] The interlayer anions of the layered composite metal hydroxide are corrosion-inhibiting anions.

[0008] Preferably, the weight ratio of the epoxy resin to the curing agent is 1:0.3-0.5.

[0009] Preferably, the weight ratio of the epoxy resin to the microbead layered composite metal hydroxide composite material is 1:0.01-0.2.

[0010] Preferably, the epoxy resin is a water-based epoxy resin.

[0011] Preferably, the curing agent is a water-based epoxy curing agent and / or an organosilicon-modified curing agent.

[0012] Preferably, the particle size of the microbeads is 0.1-500 μm, more preferably 50-150 μm.

[0013] Preferably, the corrosion-inhibiting anion is selected from MoO4 2- PO4 3- HCOO - 、CH3(CH2) 11 OSO3 - 、NO3 - and NO2 - One or more of the following.

[0014] Preferably, the metal elements in the layered composite metal hydroxide are metal M and metal N; the metal M is selected from one or more of Mg, Ni, Cu, Zn and Ca, and the metal N is selected from one or more of Al, Co, Fe, Cr and Ga.

[0015] Preferably, the preparation method of the microbead layered composite metal hydroxide composite material comprises the following steps:

[0016] (1) mixing microbeads, a metal precursor, a solvent, and a substance capable of forming carbonate ions in a solution to obtain a mixed solution, adjusting the pH value of the mixed solution to be greater than 7, and then reacting;

[0017] (2) performing solid-liquid separation and heat treatment on the material obtained in step (1);

[0018] (3) Mixing the material obtained by heat treatment in step (2) with a solution containing a corrosion-inhibiting compound, adjusting the pH value of the solution to be greater than 7, and then reacting.

[0019] Preferably, the metal precursors are a metal M precursor and a metal N precursor; the molar ratio of the metal M precursor to the metal N precursor is 1:0.2-5, calculated as metal.

[0020] Preferably, the weight ratio of the microbeads to the metal M precursor is 1:0.5-5.

[0021] Preferably, the anti-corrosion and thermal insulation coating composition further contains functional pigments.

[0022] Preferably, the weight ratio of the epoxy resin to the functional pigment is 1:0.1-0.3.

[0023] Preferably, the functional pigment is selected from one or more of titanium dioxide, ultrafine heavy calcium carbonate, calcium carbonate, barium sulfate, talc, bentonite and quartz powder.

[0024] Preferably, the anti-corrosion and thermal insulation coating composition further contains an auxiliary agent.

[0025] Preferably, the weight ratio of the epoxy resin to the auxiliary agent is 1:0.05-0.1.

[0026] Preferably, the auxiliary agent is selected from one or more of a dispersant, a defoaming agent, a thickener, a mildew preventer and an aerogel.

[0027] A second aspect of the present invention provides an anti-corrosion and thermal insulation coating, which is obtained by mixing the above-mentioned anti-corrosion and thermal insulation coating composition with water.

[0028] Preferably, the weight ratio of the epoxy resin to water is 1:0.3-0.5.

[0029] A third aspect of the present invention provides a method for preparing an anti-corrosion and thermal insulation coating, wherein the anti-corrosion and thermal insulation coating is obtained by applying the above-mentioned anti-corrosion and thermal insulation coating to the surface of a substrate and then curing it.

[0030] Preferably, the curing conditions include: a temperature of 30-60° C. and a curing time of 24-60 h.

[0031] Compared with the prior art, the technical solution of the present invention has the following advantages:

[0032] (1) In the present invention, the microbead layered composite metal hydroxide composite material has good dispersibility and good performance in capturing corrosive anions such as chloride ions. At the same time, the glass microbeads or ceramic microbeads also have heat preservation properties. Therefore, when the microbead layered composite metal hydroxide composite material is used in a coating, it can not only improve the anti-corrosion performance of the coating, but also have a heat preservation effect;

[0033] (2) The anti-corrosion and thermal insulation coating of the present invention has good corrosion protection performance for steel materials such as petrochemical and thermal pipelines at temperatures below 200°C;

[0034] (3) The technical solution described in the present invention is green and environmentally friendly, with a simple process and low cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 The figure is a test result of a neutral salt spray test of the coating prepared in Example 1 applied on a 5cm×2.5cm×0.2cm 20# steel sheet;

[0036] Figure 2 This is a test result diagram of a neutral salt spray test of the coating prepared in Comparative Example 1 applied on a 5cm×2.5cm×0.2cm 20# steel sheet;

[0037] Figure 3 This is a graph showing the electrochemical impedance test results of a 1cm×1cm×0.5cm Q235 carbon steel electrode coated with the coating prepared in Example 1 at an artificial defect of the Q235 carbon steel electrode. DETAILED DESCRIPTION

[0038] The following describes the specific embodiments of the present invention in detail with reference to the accompanying drawings. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention and are not intended to limit the present invention.

[0039] The endpoints of the ranges and any values ​​disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoints of each range, the endpoints of each range and individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered to be specifically disclosed herein.

[0040] In one aspect, the present invention provides an anti-corrosion and thermal insulation coating composition, comprising a microbead layered composite metal hydroxide composite material, an epoxy resin, and a curing agent, wherein the microbead layered composite metal hydroxide composite material comprises microbeads and a layered composite metal hydroxide coated on the surface of the microbeads;

[0041] The microbeads are glass microbeads and / or ceramic microbeads;

[0042] The interlayer anions of the layered composite metal hydroxide are corrosion-inhibiting anions.

[0043] In the present invention, there is no special requirement for the "microbeads", and either "hollow microbeads" or "solid microbeads" are acceptable.

[0044] In a preferred embodiment, the microbeads are glass microbeads and / or ceramic microbeads.

[0045] In a preferred embodiment, in order to further improve the dispersibility of the layered composite metal hydroxide, the particle size of the microbeads is 0.1-500 μm, more preferably 50-150 μm.

[0046] In the present invention, the "corrosion-inhibiting anions" refer to "ions that can undergo ion exchange with corrosive anions (such as chloride ions) and capture corrosive anions in the environment."

[0047] In a preferred embodiment, in order to further improve the performance of the layered composite metal hydroxide in capturing corrosive anions (such as chloride ions), the corrosion-inhibiting anions are selected from MoO4 2- PO4 3- HCOO - 、CH3(CH2) 11 OSO3 - 、NO3 - and NO2 - One or more of the following.

[0048] In a preferred embodiment, the weight ratio of the epoxy resin to the curing agent is 1:0.3-0.5; specifically, it can be 1:0.3, 1:0.4 or 1:0.5.

[0049] In a preferred embodiment, the weight ratio of the epoxy resin to the microbead layered composite metal hydroxide composite material is 1:0.01-0.2; specifically, it can be 1:0.01, 1:0.05, 1:0.1, 1:0.12, 1:0.15 or 1:0.2.

[0050] In a preferred embodiment, in order to improve the compatibility between the anti-corrosion and thermal insulation coating compositions, the epoxy resin is a water-based epoxy resin.

[0051] In a preferred embodiment, the curing agent is a water-based epoxy curing agent and / or an organosilicon-modified curing agent.

[0052] In a preferred embodiment, the waterborne epoxy curing agent is selected from one or more of polyamide curing agents, fatty amine curing agents and acid anhydride curing agents.

[0053] In a preferred embodiment, the organosilicon-modified curing agent is a siloxane-coupled organosilicon-modified curing agent and / or a substituted siloxane side group organosilicon-modified curing agent.

[0054] In a preferred embodiment, the metal elements in the layered composite metal hydroxide are metal M and metal N; the metal M is selected from one or more of Mg, Ni, Cu, Zn and Ca, and the metal N is selected from one or more of Al, Co, Fe, Cr and Ga.

[0055] In a preferred embodiment, the preparation method of the microbead layered composite metal hydroxide composite material comprises the following steps:

[0056] (1) mixing microbeads, a metal precursor, a solvent, and a substance capable of forming carbonate ions in a solution to obtain a mixed solution, adjusting the pH value of the mixed solution to be greater than 7, and then reacting;

[0057] (2) performing solid-liquid separation and heat treatment on the material obtained in step (1);

[0058] (3) Mixing the material obtained by heat treatment in step (2) with a solution containing a corrosion-inhibiting compound, adjusting the pH value of the solution to be greater than 7, and then reacting.

[0059] In a preferred embodiment, the method for preparing the microbead layered composite metal hydroxide composite material further comprises pre-treating the microbeads to remove grease on the surface of the microbeads.

[0060] In a specific embodiment, the microbeads are mixed with ethanol and then stirred, and then filtered, washed and dried.

[0061] In the present invention, there is no special requirement for the “substance capable of forming carbonate ions in solution”, as long as it can provide carbonate ions in the solution.

[0062] In a preferred embodiment, in step (1), the substance capable of forming carbonate ions in the solution may be carbonate, bicarbonate or carbonic acid; specifically, it may be one or more of sodium carbonate, potassium carbonate, ammonium carbonate, sodium bicarbonate and potassium bicarbonate.

[0063] In the present invention, there is no special requirement for the amount of the substance capable of forming carbonate ions in the solution, as long as microbead layered composite metal hydroxide can be obtained after solid-liquid separation in step (2) and the interlayer anions are carbonate.

[0064] In a preferred embodiment, in step (1), the metal precursors are a metal M precursor and a metal N precursor; the molar ratio of the metal M precursor to the metal N precursor is 1:0.2-5, calculated as metal; specifically, the molar ratio of the metal M precursor to the metal N precursor can be 1:0.2, 1:0.5, 1:1, 1:2, 1:3, 1:4 or 1:5.

[0065] In a preferred embodiment, in order to further improve the dispersibility of the layered composite metal hydroxide, in step (1), the weight ratio of the amount of the microbeads and the metal M precursor is 1:0.5-5. Specifically, the weight ratio of the amount of the microbeads and the metal M precursor can be 1:0.5, 1:1, 1:2, 1:3, 1:4 or 1:5.

[0066] In a preferred embodiment, in order to improve the efficiency of the reaction, in step (1), the pH value of the mixed solution is adjusted to ≥8, more preferably, the pH value of the mixed solution is adjusted to 9-10.

[0067] In a preferred embodiment, in step (2), the heat treatment conditions include: temperature of 550-650°C, time of 3-8h; specifically, the temperature can be 550°C, 600°C or 650°C; and the time can be 3h, 5h or 8h.

[0068] In the present invention, the "corrosion-inhibiting compound" refers to a substance that can provide corrosion-inhibiting anions.

[0069] In the present invention, there is no special requirement for the amount of the corrosion-inhibiting compound, as long as micro-beaded layered composite metal hydroxide can be obtained after the reaction in step (3) and the interlayer anions are corrosion-inhibiting anions.

[0070] In a preferred embodiment, in order to improve the efficiency of the reaction, in step (3), the pH value of the solution is adjusted to ≥8, more preferably, the pH value of the solution is adjusted to 9-10; specifically, it can be 9, 9.5 or 10.

[0071] In the micro-beaded layered composite metal hydroxide prepared by the method of the present invention, the intermediate product obtained by solid-liquid separation in step (2) is a micro-beaded layered composite metal hydroxide, and the interlayer anions are carbonate ions. After the intermediate product is heat-treated, the interlayer anions carbonate ions decompose to reserve holes, thereby introducing any desired corrosion-inhibiting anions into the layered composite metal hydroxide. Since the carbonate ions have a strong binding force with the cationic layer of the layered composite metal hydroxide, the micro-beaded layered composite metal hydroxide composite material prepared by the method of the present invention has no special requirements for the anions of the metal precursor.

[0072] In a preferred embodiment, in order to impart color to the coating prepared using the anti-corrosion and thermal insulation coating composition and improve its performance, the anti-corrosion and thermal insulation coating composition further contains functional pigments.

[0073] In a preferred embodiment, the weight ratio of the epoxy resin to the functional pigment is 1:0.1-0.3; specifically, the weight ratio of the epoxy resin to the functional pigment can be 1:0.1, 1:0.2 or 1:0.3.

[0074] In a preferred embodiment, the functional pigment is selected from one or more of titanium dioxide, ultrafine heavy calcium carbonate, calcium carbonate, barium sulfate, talc, bentonite and quartz powder.

[0075] In a preferred embodiment, in order to further improve the overall performance of the coating prepared using the anti-corrosion and thermal insulation coating composition, the anti-corrosion and thermal insulation coating composition further contains an additive.

[0076] In a preferred embodiment, the weight ratio of the epoxy resin to the auxiliary agent is 1:0.05-0.1; specifically, the weight ratio of the epoxy resin to the auxiliary agent can be 1:0.05, 1:0.08 or 1:0.1.

[0077] In a preferred embodiment, the auxiliary agent is selected from one or more of a dispersant, a defoaming agent, a thickener, a mildew preventer and an aerogel.

[0078] According to some embodiments of the present invention, the auxiliary agent is a dispersant, a defoaming agent, a thickener, a mildew preventer and an aerogel.

[0079] In a specific embodiment, based on the weight of the additive being 100%, the amount of the dispersant is 20wt%, the amount of the defoamer is 3wt%, the amount of the thickener is 20wt%, the amount of the mildewproof agent is 7wt%, and the amount of the aerogel is 50wt%.

[0080] A second aspect of the present invention provides an anti-corrosion and thermal insulation coating, which is obtained by mixing the above-mentioned anti-corrosion and thermal insulation coating composition with water.

[0081] The anti-corrosion and thermal insulation coating described in the present invention is obtained by mixing the anti-corrosion and thermal insulation coating composition described in the present invention with water, and has good thermal insulation performance and anti-corrosion performance. The anti-corrosion and thermal insulation coating composition contains micro-bead layered composite metal hydroxides, and the micro-bead layered composite metal hydroxide composite material has good dispersion performance and the ability to capture corrosive anions (such as chloride ions) by coating the layered composite metal hydroxide on the surface of the micro-beads, which makes the anti-corrosion and thermal insulation coating described in the present invention have better thermal insulation and anti-corrosion performance.

[0082] In a preferred embodiment, in order to better fuse the epoxy resin and the curing agent and make the viscosity of the anti-corrosion and thermal insulation coating more suitable for preparing an anti-corrosion and thermal insulation coating, the weight ratio of the epoxy resin and water is 1:0.3-0.5; specifically, the weight ratio of the epoxy resin and water can be 1:0.3, 1:0.4 or 1:0.5.

[0083] In a preferred embodiment, the preparation method of the anti-corrosion thermal insulation coating comprises the following steps:

[0084] A1: Mix the additive and water. The mixing conditions include: stirring rate of 500-800 r / min and stirring time of 5-10 min;

[0085] A2: Mixing the microbead layered composite metal hydroxide composite material, epoxy resin and functional pigment with the material obtained in step A1. The mixing conditions include: a stirring rate of 200-500 r / min and a stirring time of 20-30 min.

[0086] A third aspect of the present invention provides a method for preparing an anti-corrosion and thermal insulation coating, wherein the anti-corrosion and thermal insulation coating is obtained by applying the above-mentioned anti-corrosion and thermal insulation coating to the surface of a substrate and then curing it.

[0087] In a preferred embodiment, the curing conditions include: a temperature of 30-60°C and a time of 24-60 hours; specifically, the temperature can be 30°C, 40°C, 50°C or 60°C; and the time can be 24 hours, 36 hours, 48 ​​hours or 60 hours.

[0088] The following examples further illustrate the anti-corrosion and thermal insulation coating composition, the coating, and the preparation method of the coating according to the present invention. The examples are implemented based on the technical solution of the present invention and provide detailed implementation methods and specific operating processes, but the scope of protection of the present invention is not limited to the following examples.

[0089] Table 1

[0090]

[0091]

[0092]

[0093] Example 1

[0094] The specific selection and dosage of raw materials are shown in Table 1;

[0095] Preparation of microbead layered composite metal hydroxide composite material M1:

[0096] (1) Ceramic microbeads and ethanol were mixed and stirred, and then filtered, washed and dried after stirring for 30 minutes. 100 mg of ceramic microbeads with a particle size of 100-150 μm after drying were dispersed in 50 mL of water, stirred at 150 r / min for 30 minutes, and after uniform dispersion, 0.1 g of anhydrous sodium carbonate was added, and ultrasonicated at 500 W power for 5 minutes to obtain solution A1; 0.25 g of magnesium nitrate hexahydrate and 0.18 g of aluminum nitrate nonahydrate were dispersed in 20 mL of water, and ultrasonicated at 500 W power for 10 minutes to obtain solution B1; solution B1 was slowly added dropwise to solution A1 for 20 minutes, and a sodium hydroxide solution with a concentration of 1 M was added dropwise at the same time to adjust the pH value of the mixed solution to 9, and then reacted. After the addition was completed, the mixture was stirred at 150 r / min for 60 minutes;

[0097] (2) The material obtained in step (1) was filtered and washed to obtain an intermediate material S1 (SiO2@Mg-AlCO3), and then the intermediate material S1 was heat-treated at 550°C under vacuum conditions for 6 hours;

[0098] (3) The material obtained in step (2) was dispersed in 50 mL of a 3 mg / mL sodium nitrite solution, the pH value of the solution was adjusted to 9, and then the reaction was carried out, stirred at 150 r / min for 5 h, and then filtered, washed and dried to obtain the final product, a microbead layered composite metal hydroxide composite material M1 (SiO2@Mg-AlNO2).

[0099] Preparation of anti-corrosion thermal insulation coating S1:

[0100] A1: Mix the additive and water. The mixing conditions include: stirring rate of 500 r / min and stirring time of 8 min.

[0101] A2: adding the microbead layered composite metal hydroxide composite material, epoxy resin and functional pigment to the mixed material of step A1 and mixing them. The mixing conditions include: stirring rate of 200 r / min and stirring time of 30 min.

[0102] Example 2

[0103] Preparation of microbead layered composite metal hydroxide composite material M2:

[0104] The microbead layered composite metal hydroxide composite material M2 was prepared in the same manner as in Example 1, except that in step (1), the pH value of the mixed solution was adjusted to 10, to obtain the final product, microbead layered composite metal hydroxide composite material M2 (SiO2@Mg-AlNO2).

[0105] The specific selection and dosage of raw materials are shown in Table 1;

[0106] Preparation of anti-corrosion thermal insulation coating S2:

[0107] A1: The additive and 20 parts by weight of water were mixed under the following mixing conditions: stirring rate of 600 r / min and stirring time of 5 min;

[0108] A2: adding the microbead layered composite metal hydroxide composite material, epoxy resin and functional pigment to the mixed material of step A1 and mixing them. The mixing conditions include: stirring rate of 300 r / min and stirring time of 30 min.

[0109] Example 3

[0110] The specific selection and dosage of raw materials are shown in Table 1;

[0111] Preparation of anti-corrosion thermal insulation coating S3:

[0112] A1: Mix the additive and water. The mixing conditions include: stirring rate of 700 r / min and stirring time of 8 min.

[0113] A2: adding the microbead layered composite metal hydroxide composite material, epoxy resin and functional pigment to the mixed material of step A1 and mixing them. The mixing conditions include: stirring rate of 400 r / min and stirring time of 30 min.

[0114] Example 4

[0115] Preparation of microbead layered composite metal hydroxide composite material M3:

[0116] The microbead layered composite metal hydroxide composite material M3 was prepared in the manner of Example 1, except that in step (1), ferric nitrate nonahydrate was used instead of aluminum nitrate nonahydrate to obtain the final product, microbead layered composite metal hydroxide composite material M3 (SiO2@Mg-Fe NO2).

[0117] The specific selection and dosage of raw materials are shown in Table 1;

[0118] Preparation of anti-corrosion thermal insulation coating S4:

[0119] A1: Mix the additive and water. The mixing conditions include: stirring rate of 800 r / min and stirring time of 5 min.

[0120] A2: adding the microbead layered composite metal hydroxide composite material, epoxy resin and functional pigment to the mixed material of step A1 and mixing them. The mixing conditions include: stirring rate of 500 r / min and stirring time of 20 min.

[0121] Example 5

[0122] Preparation of microbead layered composite metal hydroxide composite material M4:

[0123] The microbead layered composite metal hydroxide composite material M4 was prepared in the manner of Example 1, except that in step (1), nickel nitrate hexahydrate was used instead of magnesium nitrate hexahydrate to obtain the final product, microbead layered composite metal hydroxide composite material M4 (SiO2@Ni-AlNO2).

[0124] The specific selection and dosage of raw materials are shown in Table 1;

[0125] Preparation of anti-corrosion thermal insulation coating S5:

[0126] A1: Mix the additive and water. The mixing conditions include: stirring rate of 500 r / min and stirring time of 8 min.

[0127] A2: adding the microbead layered composite metal hydroxide composite material, epoxy resin and functional pigment to the mixed material of step A1 and mixing them. The mixing conditions include: stirring rate of 200 r / min and stirring time of 40 min.

[0128] Example 6

[0129] Preparation of microbead layered composite metal hydroxide composite material M5:

[0130] A microbeaded layered composite metal hydroxide composite material M5 was prepared in the manner of Example 1, except that in step (3), 50 mL of a 3 mg / mL sodium molybdate solution was used instead of 50 mL of a 3 mg / mL sodium nitrite solution to obtain the final product, a microbeaded layered composite metal hydroxide composite material M5 (SiO2@Mg-AlMoO4).

[0131] The specific selection and dosage of raw materials are shown in Table 1;

[0132] Preparation of anti-corrosion thermal insulation coating S6:

[0133] A1: Mix the additive and water. The mixing conditions include: stirring rate of 600 r / min and stirring time of 15 min.

[0134] A2: adding the microbead layered composite metal hydroxide composite material, epoxy resin and functional pigment to the mixed material of step A1 and mixing them. The mixing conditions include: stirring rate of 300 r / min and stirring time of 10 min.

[0135] Example 7

[0136] Preparation of microbead layered composite metal hydroxide composite material M6:

[0137] A microbeaded layered composite metal hydroxide composite material M6 was prepared in the manner of Example 1, except that in step (3), the pH value of the solution was adjusted to 10, and 50 mL of a 5 mg / mL sodium phosphate solution was used instead of 50 mL of a 3 mg / mL sodium nitrite solution to obtain the final product, a microbeaded layered composite metal hydroxide composite material M6 (SiO2@Mg-AlPO4).

[0138] The specific selection and dosage of raw materials are shown in Table 1;

[0139] Preparation of anti-corrosion thermal insulation coating S7:

[0140] A1: Mix the additive and water. The mixing conditions include: stirring rate of 700 r / min and stirring time of 30 min.

[0141] A2: adding the microbead layered composite metal hydroxide composite material, epoxy resin and functional pigment to the mixed material of step A1 and mixing them. The mixing conditions include: stirring rate of 400 r / min and stirring time of 20 min.

[0142] Example 8

[0143] The specific selection and dosage of raw materials are shown in Table 1;

[0144] Preparation of anti-corrosion thermal insulation coating S8:

[0145] A1: Mix the additive and water. The mixing conditions include: stirring rate of 800 r / min and stirring time of 10 min.

[0146] A2: adding the microbead layered composite metal hydroxide composite material, epoxy resin and functional pigment to the mixed material of step A1 and mixing them. The mixing conditions include: stirring rate of 500 r / min and stirring time of 60 min.

[0147] Example 9

[0148] Preparation of microbead layered composite metal hydroxide composite material M7:

[0149] The micro-beaded layered composite metal hydroxide composite material M7 was prepared in the same manner as in Example 1, except that in step (3), the pH value of the solution was adjusted to 8, to obtain the final product, micro-beaded layered composite metal hydroxide composite material M7 (SiO2@Mg-AlNO2).

[0150] The specific selection and dosage of raw materials are shown in Table 1;

[0151] Preparation of anti-corrosion thermal insulation coating S9:

[0152] A1: Mix the additive and water. The mixing conditions include: stirring rate of 500 r / min and stirring time of 20 min.

[0153] A2: adding the microbead layered composite metal hydroxide composite material, epoxy resin and functional pigment to the mixed material of step A1 and mixing them. The mixing conditions include: stirring rate of 200 r / min and stirring time of 50 min.

[0154] Example 10

[0155] Preparation of microbead layered composite metal hydroxide composite material M8:

[0156] A microbead layered composite metal hydroxide composite material M8 was prepared in the manner of Example 1, except that in step (1), the pH value of the mixed solution was adjusted to 10, nickel nitrate hexahydrate was used instead of magnesium nitrate hexahydrate, and iron nitrate nonahydrate was used instead of aluminum nitrate nonahydrate; in step (3), the pH value of the solution was adjusted to 10 to obtain the final product, ceramic microbead Mg-Al layered composite metal hydroxide composite material M8 (SiO2@Ni-Fe NO2).

[0157] The specific selection and dosage of raw materials are shown in Table 1;

[0158] Preparation of anti-corrosion thermal insulation coating S10:

[0159] A1: Mix the additive and water. The mixing conditions include: stirring rate of 600 r / min and stirring time of 30 min.

[0160] A2: adding the microbead layered composite metal hydroxide composite material, epoxy resin and functional pigment to the mixed material of step A1 and mixing them. The mixing conditions include: stirring rate of 300 r / min and stirring time of 30 min.

[0161] Comparative Example 1

[0162] Preparation of anti-corrosion thermal insulation coating S11:

[0163] The process is carried out in the same manner as in Example 1, except that the raw material does not contain the microbead layered composite metal hydroxide composite material M1.

[0164] Comparative Example 2

[0165] Preparation of anti-corrosion thermal insulation coating S12:

[0166] The method of Example 1 was followed, except that the microbead layered composite metal hydroxide composite material M1 was replaced by ceramic microbeads of the same weight.

[0167] Comparative Example 3

[0168] Preparation of anti-corrosion thermal insulation coating S13:

[0169] The method of Example 1 was followed, except that the microbead layered composite metal hydroxide composite material M1 was replaced by the same weight of Mg-Al layered composite metal hydroxide.

[0170] Test Case

[0171] (1) The coatings prepared in Example 1 and Comparative Example 1 were coated on 20# steel sheets of 5 cm × 2.5 cm × 0.2 cm, cured at 30°C for 48 h, and then immersed in a 5 wt% sodium chloride solution for a neutral salt spray test. Figure 1 The figure is a test result of a neutral salt spray test of the coating prepared in Example 1 on a 5cm×2.5cm×0.2cm 20# steel sheet. Figure 2 This is a test result diagram of the neutral salt spray test of the coating prepared in Example 1 applied on a 5cm×2.5cm×0.2cm 20# steel sheet; wherein, Figure 1 (a) is the test result after immersion for 100 hours. Figure 1 (b) is the test result after immersion for 300 hours. Figure 1 (c) is the test result after 1000 hours of immersion; Figure 2 (a) is the test result after immersion for 100 hours. Figure 2 (b) is the test result after immersion for 300 hours. Figure 2 (c) is the test result after 1000 hours of immersion;

[0172] Depend on Figure 1 and Figure 2 It can be seen that the coating prepared by adding the micro-beaded layered composite metal hydroxide in Example 1 has better anti-corrosion performance against metals than the coating prepared by not adding the micro-beaded layered composite metal hydroxide in Comparative Example 1.

[0173] (2) The anti-corrosion performance of the coatings prepared in Examples 1-10 and Comparative Examples 1-3 was tested in the following manner: the sample to be tested was coated on a 1 cm × 1 cm × 0.5 cm Q235 carbon steel electrode, cured at 30°C for 48 hours, and then immersed in a 3.5 wt% sodium chloride solution to characterize the electrochemical impedance of the artificial defect. The test results are shown in Table 2. Figure 3 The electrochemical impedance spectroscopy test results of the coating prepared in Example 1 applied to a 1cm×1cm×0.5cm Q235 carbon steel electrode at an artificial defect of the Q235 carbon steel electrode are shown in FIG. Figure 3 (a) is the electrochemical impedance spectroscopy result of the artificial defect of Q235 carbon steel electrode after immersion for 2 hours. Figure 3(b) is the electrochemical impedance spectroscopy result of the artificial defect of Q235 carbon steel electrode after immersion for 12 hours. Figure 3 (c) is the electrochemical impedance spectroscopy test result of the artificial defect of Q235 carbon steel electrode after immersion for 24 hours;

[0174] Depend on Figure 3 (a) It can be seen that the minimum impedance value at the artificial defect after immersion for 2 hours is 2.15×10 5 Ω; by Figure 3 (b) It can be seen that the minimum impedance value after immersion for 12 hours is 2.29×10 5 Ω; by Figure 3 (c) It can be seen that the minimum impedance value after immersion for 24 hours is 2.38×10 5 Ω; It can be seen that with the extension of time, the impedance of the artificial defect of the Q235 carbon steel electrode increases, indicating that the nitrite ions released by the micro-beaded layered composite metal hydroxide in the coating can promote the formation of a dense oxide layer on the steel surface, preventing the Q235 carbon steel electrode from further serious corrosion.

[0175] (3) The thermal conductivity of the coatings prepared in Examples 1-10 and Comparative Examples 1-3 was tested in the following manner: the sample to be tested was coated on a 1 cm × 1 cm × 0.5 cm Q235 carbon steel electrode, cured at 30°C for 48 h, and then immersed in a 3.5 wt% sodium chloride solution for 24 h. After being taken out and dried, the thermal conductivity of the coating was tested using a thermal conductivity meter. The test results are shown in Table 2.

[0176] Table 2

[0177]

[0178]

[0179] It can be seen from the results in Table 2 that the coatings prepared with the anti-corrosion and thermal insulation coatings of the present invention have good thermal insulation and anti-corrosion properties, especially the coatings prepared with the coatings prepared in Examples 1-3, which have even better thermal insulation and anti-corrosion functions.

[0180] The preferred embodiments of the present invention have been described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, various simple variations of the technical solution of the present invention may be made, including combining the various technical features in any other appropriate manner. These simple variations and combinations should also be regarded as disclosed in the present invention and fall within the scope of protection of the present invention.

Claims

1. An anticorrosion and thermal insulation coating composition, characterized in that: The anticorrosion and thermal insulation coating composition contains a micro-bead layered composite metal hydroxide composite material, an epoxy resin and a curing agent, wherein the micro-bead layered composite metal hydroxide composite material includes micro-beads and layered composite metal hydroxides coated on the surface of the micro-beads; The microbeads are glass microbeads and / or ceramic microbeads; The interlayer anions of the layered composite metal hydroxide are corrosion-inhibiting anions.

2. The anticorrosion and thermal insulation coating composition according to claim 1, characterized in that: The weight ratio of the epoxy resin to the curing agent is 1:0.3-0.5; Preferably, the weight ratio of the epoxy resin to the microsphere layered composite metal hydroxide composite material is 1:0.01-0.

2.

3. The anticorrosion and thermal insulation coating composition according to claim 1 or 2, characterized in that: The epoxy resin is a water-based epoxy resin; Preferably, the curing agent is a water-based epoxy curing agent and / or a silicone-modified curing agent.

4. The anticorrosion and thermal insulation coating composition according to any one of claims 1 to 3, characterized in that: The particle size of the microbeads is 0.1-500 μm, more preferably 50-150 μm.

5. The anticorrosion and thermal insulation coating composition according to any one of claims 1 to 4, characterized in that: The corrosion-inhibiting anion is selected from MoO4 2- PO4 3- HCOO - 、CH3(CH2) 11 OSO3 - 、NO3 - and NO2 - One or more of the following.

6. The anticorrosion and thermal insulation coating composition according to any one of claims 1 to 5, characterized in that: The metal elements in the layered composite metal hydroxide are metal M and metal N; The metal M is selected from one or more of Mg, Ni, Cu, Zn and Ca, and the metal N is selected from one or more of Al, Co, Fe, Cr and Ga.

7. The anticorrosion and thermal insulation coating composition according to any one of claims 1 to 6, characterized in that: The preparation method of the microbead layered composite metal hydroxide composite material comprises the following steps: (1) mixing microbeads, a metal precursor, a solvent, and a substance capable of forming carbonate ions in a solution to obtain a mixed solution, adjusting the pH value of the mixed solution to greater than 7, and then reacting; (2) performing solid-liquid separation and heat treatment on the material obtained in step (1); (3) Mixing the material obtained by heat treatment in step (2) with a solution containing a corrosion-inhibiting compound, adjusting the pH value of the solution to greater than 7, and then reacting.

8. The anticorrosion and thermal insulation coating composition according to claim 7, characterized in that: The metal precursors are metal M precursors and metal N precursors; The molar ratio of the metal M precursor to the metal N precursor is 1:0.2-5, calculated as metal.

9. The anticorrosion and thermal insulation coating composition according to claim 7 or 8, characterized in that: The weight ratio of the microbeads to the metal M precursor is 1:0.5-5.

10. The anticorrosion and thermal insulation coating composition according to any one of claims 1 to 9, characterized in that: The anticorrosion and thermal insulation coating composition further contains functional pigments; Preferably, the weight ratio of the epoxy resin to the functional pigment is 1:0.1-0.3; Preferably, the functional pigment is selected from one or more of titanium dioxide, ultrafine heavy calcium, calcium carbonate, barium sulfate, talc, bentonite and quartz powder.

11. The anticorrosion and thermal insulation coating composition according to any one of claims 1 to 10, characterized in that: The anticorrosion and thermal insulation coating composition further contains an auxiliary agent; Preferably, the weight ratio of the epoxy resin to the auxiliary agent is 1:0.05-0.1; Preferably, the auxiliary agent is selected from one or more of a dispersant, a defoamer, a thickener, a mildew preventer and an aerogel.

12. An anti-corrosion and thermal insulation coating, characterized in that: The anti-corrosion and thermal insulation coating is obtained by mixing the anti-corrosion and thermal insulation coating composition according to any one of claims 1 to 11 with water.

13. The anticorrosion and thermal insulation coating according to claim 12, characterized in that: The weight ratio of the epoxy resin to water is 1:0.3-0.

5.

14. A method for preparing an anti-corrosion and thermal insulation coating, characterized in that: The anti-corrosion and thermal insulation coating is obtained by applying the anti-corrosion and thermal insulation coating according to claim 12 or 13 to the surface of a substrate and then curing it.

15. The method according to claim 14, characterized in that The curing conditions include: temperature of 30-60°C and time of 24-60h.

Citation Information

Patent Citations

  • Water-based energy-saving and thermal insulation coating for petrochemical oil tank and preparation method thereof

    CN104877484B

  • Vacuum ceramic microsphere thermal insulation and anti-corrosion coating for steel structure equipment and its preparation method

    CN111019424B

  • A thermal insulation coating and its preparation method

    CN111534131B

  • Method for preparing colored heat-insulation paint

    CN105505074A

  • Preparation method and application core-shell structure laminated double-metal hydroxide composite particles

    CN106334524A